2020
DOI: 10.1007/s00394-020-02188-2
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Nordic diet and risk of disease death among men: the Kuopio Ischaemic Heart Disease Risk Factor Study

Abstract: Purpose To investigate the association between healthy Nordic diet and risk of disease death in middle-aged and older men from eastern Finland. Methods A total of 1547 men aged 42-60 years and free of cardiovascular disease (CVD), cancer and type 2 diabetes at baseline in 1984-1989 were included. Diet was assessed with 4-day food records at baseline and the healthy Nordic diet score was calculated based on the Baltic Sea Diet Score. The incidence of death was assessed by a computer linkage to the national caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…An estimate of the average number of hours slept at night was obtained using self-administered questionnaires [21]. Slightly modified Baltic Sea Diet Scores (BSDS) were calculated based on four-day food records collected at baseline [22].…”
Section: Methodsmentioning
confidence: 99%
“…An estimate of the average number of hours slept at night was obtained using self-administered questionnaires [21]. Slightly modified Baltic Sea Diet Scores (BSDS) were calculated based on four-day food records collected at baseline [22].…”
Section: Methodsmentioning
confidence: 99%
“…Because of the limited number of studies, our aim was to examine the association between healthy Nordic diet, based on a modified Baltic Sea Diet Score, and risk of CHD in the Kuopio Ischaemic Heart Disease Risk Factor Study (KIHD), a population of middle-aged and older men from eastern Finland. We have previously reported that a low adherence to a healthy Nordic diet was associated with a higher risk of cardiovascular disease death in this study population (24) . We additionally investigated the associations with risk factors of CHD, including blood pressure, serum lipid profile and serum CRP.…”
Section: Introductionmentioning
confidence: 51%
“…Possible multicollinearity was checked using variance inflation factors, which all were under 2, indicating no multicollinearity. The analyses were adjusted for relevant covariates, based on established risk factors for CHD and our previous investigation of the association between a healthy Nordic diet score and mortality risk (24) : The Model 1 included age (years), examination year and energy intake (kcal/day). The multivariable Model 2 included variables in the Model 1 and pack-years of smoking, leisure-time physical activity (kcal/day), education (years), marital status (yes/no), income (euros/year), and use of medications (hypercholesterolemia and hypertension medication and aspirin).…”
Section: Discussionmentioning
confidence: 99%
“…The index, considered as a validated measure of diet quality based on commonly consumed foods in Nordic countries, summarizes six foods and food group variables and three nutrient variables (supplementary material 1). [23] We excluded alcohol from the healthy HND index, because we used alcohol consumption as a separate factor. Physical activity was assessed by several methods including self-recordings and interviews.…”
Section: Variables Measurementmentioning
confidence: 99%